2008
DOI: 10.1007/s10928-008-9088-2
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to handling pharmacodynamic baseline responses

Abstract: A few approaches for handling baseline responses are available for use in pharmacokinetic (PK)-pharmacodynamic (PD) analysis. They include: (method 1-B1) estimation of the typical value and interindividual variability (IIV) of baseline in the population, (B2) inclusion of the observed baseline response as a covariate acknowledging the residual variability, (B3) a more general version of B2 as it also takes the IIV of the baseline in the population into account, and (B4) normalization of all observations by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 13 publications
1
75
0
Order By: Relevance
“…Because change from baseline VA at the study end was our end point of interest, unbiased estimates of initial or baseline BCVA values gi0 were crucial 23. We modeled baseline VA gi0 as normally distributed around observed value BVA i : gi0=BVAi+η1,i.…”
Section: Resultsmentioning
confidence: 99%
“…Because change from baseline VA at the study end was our end point of interest, unbiased estimates of initial or baseline BCVA values gi0 were crucial 23. We modeled baseline VA gi0 as normally distributed around observed value BVA i : gi0=BVAi+η1,i.…”
Section: Resultsmentioning
confidence: 99%
“…The typical value of uNTx 0 /Cr 0 was 49.2 nmol/L/mmol/L and its associated BSV was 77%. Given the uNTx/Cr data available and the several approaches suggested to handle baseline values (37), an attempt was made to estimate uNTx 0 /Cr 0 , its associated variability, and to acknowledge the uNTx/Cr RV. However, the goodness-offit was not improved and the running time was substantially increased with respect to the model that fixed uNTx 0 /Cr 0 to the observed individual value.…”
Section: Resultsmentioning
confidence: 99%
“…The authors would like to emphasize that the baseline normalization is only beneficial for diagnostic purposes. It has previously been shown that there are important advantages with estimating a baseline parameter rather than modeling baseline-normalized data (20).…”
Section: Discussionmentioning
confidence: 99%